Embolisation of Contraceptive Implants to the Pulmonary Arterial System: A Series of Three Cases from a Tertiary Thoracic Surgery Unit - Hughes, Theo; Gundle, Leo; Pather, Micayla; Khademi, Sara; Chan, Sophia; Chen, Shuya; Weedle, Rebecca; Bille, Andrea; Ashrafian, Leanne; Pilling, John (The Thoracic and Cardiovascular Surgeon, 2025)
Contraceptive implants are widely used for long-acting reversible contraception (LARC) due to their high efficacy and convenience. However, complications including migration and, rarely, embolisation to the pulmonary arterial system have been reported. This case series presents three cases of contraceptive implant embolisation to the pulmonary arterial system, managed at a tertiary thoracic surgery unit between 2021 and 2024. Different surgical management was performed in all three cases influenced by factors including: length of time since possible embolisation, implant location, and suspected degree of endothelialisation. The cases highlight challenges in surgical management of embolized contraceptive implants, focusing on arteriotomy and anatomical resection approaches. The importance of prompt diagnosis, multidisciplinary decision-making, and necessity for further research to establish guidelines for the management of embolized contraceptive implants is exemplified. Suppliers should be aware of this rare complication and consider methods to prevent its occurrence.
Keywords: minimally invasive surgery (includes port access; minithoracotomy); pulmonary arteries/veins; pulmonary embolism; surgery/incisions; thoracoscopy/VATS